Exercise, cancer and cardiovascular disease: what should clinicians advise?. Issue 2 (3rd September 2020) - Zimmerman, Allison; Planek, Maria Isabel Camara; Chu, Catherine; Oyenusi, Opeyemi; Paner, Agne; Reding, Kerryn; Skeete, Jamario; Clark, Brian; Okwuosa, Tochi M.
Abstract : Cardiovascular disease is one of the leading causes of morbidity and mortality in persons with cancer. The elevated risk is thought to derive from the combination of cardiovascular risk factors and direct cardiotoxicity from cancer therapies. Exercise may be a potential strategy to counteract these toxicities and maintain cardiovascular reserve. In this article, we review the evidence for the potential cardioprotective effects of exercise training in cancer patients before, during, and following treatment. We also propose a patient-tailored approach for the development of targeted prescriptions based on individual exercise capacity and cardiovascular reserve.